The effect of macroeconomic variables on the poverty rate in Indonesia - Nabila, Rifda (Nur Science Institute, 2021)
Poverty is one of the main issues that is widely discussed in developing countries, including Indonesia. In addition, poverty is a benchmark for socio-economic conditions in assessing the success of development carried out by the state. This study aims to determine the relationship between Gross Regional Domestic Product (GRDP), Human Development Index (HDI), and unemployment on poverty in Indonesia. The data used are cross-sectional data from 34 provinces during 2020. The analysis used is a multiple linear regression approach. The results of the study found that the Human Development Index (HDI) had a negative effect on poverty. Meanwhile, Gross Regional Domestic Product (GDP) and unemployment have no effect on poverty. The novelty of this research is to confirm and confirm several research results related to the factors that influence poverty in Indonesia.